Manual removal of placenta in women having unpredictable adherent placenta. Issue 1 (19th September 2018) - Furukawa, Seishi; Fujisaki, Midori; Maki, Yohei; Oohashi, Masanao; Doi, Koutarou; Sameshima, Hiroshi
Abstract: Aim: Our aim is to provide expected outcomes for undergoing manual removal of placenta (MROP) following vaginal delivery in women having an unpredictable adherent placenta (AP). Methods: The data were obtained from four hospitals in Miyazaki Prefecture, Japan. We used propensity score‐matched (1:1) analysis to match women who underwent MROP with women who did not undergo MROP (control). Total blood loss and hemorrhagic rate used as a ratio of women who reached a certain amount of blood loss were compared. Subgroup analysis was undertaken and was dependent on the presence of AP. We found the cut‐off value of blood loss for detecting AP. Results: Thirty‐seven MROP cases were identified. Total blood loss and hemorrhagic rate differed significantly between MROP cases and controls; 95% of controls had blood loss of 1000 mL or less, whereas for the MROP cases, it was 14%. Fourteen MROP cases were diagnosed with AP. The hemorrhagic rate differed significantly between MROP cases with and without AP ( n = 19); 79% of MROP cases without AP had blood loss of 2000 mL or less, whereas for the MROP cases with AP, it was 7%. There were seven incidents of hysterectomy and two of arterial embolization in MROP cases with AP. Through receiver operating characteristic curve analysis, 2035 mL of blood loss was determined to be the optimal cut‐off value for detecting AP. Conclusion: The incidence of unpredictable AP in MROP cases was as high as 38%. The morbidity of MROP cases with unpredictable AP was severe. MROP should be prohibited in the absence of appropriate hemostatic preparations.